Measurements and classifications in musculoskeletal radiology - Waldt, Simone; Wörtler, Klaus; Eiber, Matthias; Telger, Terry C (Georg Thieme Verlag, 2014)
For all radiology residents and practitioners faced with mastering the huge array of image-based measurements and classifications in orthopedics, Measurements and Classifications in Musculoskeletal Radiology fills an important gap.Highly practical and accessible, it presents the measurement techniques, classification systems, scoring methods, and reference values currently in use in musculoskeletal radiology in a single, comprehensive volume, stressing the significance of each for determining the stage, diagnosis, treatment, and prognosis of a wide range of orthopedic disorders.Special all currently fragmented information on musculoskeletal radiology measurements and classification systems (excluding bone fractures) into one convenient text eliminating the need for time-consuming memorization and literature searchesCovers all established measurement methods made using conventional and sectional imaging techniquesIncludes nearly 400 detailed illustrations and radiological images showing reference lines, markings, orientations, and angles, with key values indicated throughoutLogically structured by anatomic sites and pathologies for easy access to information, with clinical pearls highlighted in every chapterOffers practical guidance on the relevance and reliability of each imaging method, preferred techniques for specific diseases, and tips for achieving the clearest and most precise measurement resultsIdeal for use at the radiology workstation, this generously illustrated resource will also be helpful to orthopedic specialists and trauma surgeons who utilize radiologic measurements and classifications for optimal diagnostic and treatment decisions.
Keywords: Diagnostic Imaging; muskuloskeletální nemoci; Musculoskeletal Diseases; diagnostické zobrazování; ortopedie; radiologie, nukleární medicína a zobrazovací metody